Chronic iron overload induces vascular dysfunction in resistance pulmonary arteries associated with right ventricular remodeling in rats. (1st October 2018) - Bertoli, Sabrina Rodrigues; Marques, Vinicius Bermond; Rossi, Emilly Martinelli; Krause, Maiara; Carneiro, Maria Tereza Weitzel Dias; Simões, Maylla Ronacher; dos Santos, Leonardo
Graphical abstract: Highlights: Chronic iron overload induced right ventricle dysfunction and hypertrophy in rats. There were inward remodelling and altered reactivity of the pulmonary arteries. Iron also increased pulmonary oxidative stress and reduced NO bioavailability. Local AT1 activation was liable for increasing oxidative stress during iron overload. There should be a benefit of in vivo blockade of the AT1 under these conditions. Abstract: Although iron excess is toxic to the vasculature and even that pulmonary hypertension has been reported in this scenario, the role of iron overload per se remains to be clarified. This study aimed to test the effects of chronic iron-overload in rats on the morphophysiology of resistance pulmonary arteries (RPA) and right ventricle (RV) remodeling. Rats were injected with saline or iron-dextran (10, 100 and 200 mg/kg/day i.p.) for 28 days. Our results indicated increased circulating iron with significant lung deposits. Moreover, rats treated with the highest dose exhibited RV dysfunction and hypertrophy; inward remodeling and increased vasoconstriction of the RPA. Vascular hyperreactivity was accompanied by reduced nitric oxide (NO), and was reversed by incubation with Dimethylsulfoxide, Catalase and Tempol. The NADPH oxidase subunit gp91phox was increased due to iron-overload, and incubation with angiotensin II type-1 receptor (AT1) antagonist losartan not only reduced oxidative stress but also restored vascular function. Thus, we concluded that AT1 pathway plays a role in pulmonary vascular dysfunction by increasing oxidative stress and reducing NO bioavailability, thereby contributing to vascular remodeling and pulmonary hypertension of iron-overload. This finding should instigate future studies on the beneficial impacts of in vivo blockade of AT1 receptor under iron overload.